Where have they gone? – A discussion on the balancing act of female doctors between work and family - Jerg-Bretzke, Lucia (German Medical Science GMS Publishing House, 2012)
Goals: The increasing number of vacant positions for doctors increasingly puts the issue of reconciling work and family into the spotlight in companies, hospitals and universities, as increased expectations of a better work-life balance are seen as one of the reasons for these vacancies. Highly qualified professionals are trained, but not available to the labour market. The aim is to summarise what difficulties doctors who want to have a family and their potential employers must face. Methods: The following articles show the current state of research and potential starting points for an optimisation of the medical profession from a family-friendly perspective and intend to stimulate debate. Results: Some basic steps towards better work-life balance have already been taken, such as the provision of childcare places and the increasing availability of more flexible working patterns. But it seems that these measures, since they have been implemented neither sufficiently nor universally, do not suffice to secure the next generation of staff. Especially women in leadership positions are still rare to find. Conclusions: Both male and female doctors want better quality of life by achieving a better work-life balance. The expansion of family-friendly services is seen as a necessary step to allow female doctors to successfully combine work and family.